Rapid, Quantitative, High-Sensitive Detection of Escherichia coli O157:H7 by Gold-Shell Silica-Core Nanospheres-Based Surface-Enhanced Raman Scattering Lateral Flow Immunoassay - Shi, Luoluo; Xu, Ling; Xiao, Rui; Zhou, Zihui; Wang, Chongwen; Wang, Shengqi; Gu, Bing (Frontiers in Microbiology, 2020)
Escherichia coli O157:H7 is regarded as one of the most harmful pathogenic microorganisms related to foodborne diseases. This paper proposes a rapid-detection biosensor for the sensitive and quantitative analysis of E. coli O157:H7 in biological samples by surface-enhanced Raman scattering (SERS)-based lateral flow immunoassay (LFIA). A novel gold-shell silica-core (SiO2/Au) nanosphere (NP) with monodispersity, good stability, and excellent SERS activity was utilized to prepare high-performance tags for the SERS-based LFIA system. The SiO2/Au SERS tags, which were modified with two layers of Raman reporter molecules and monoclonal antibodies, effectively bind with E. coli O157:H7 and form sandwich immune complexes on the test lines. E. coli O157:H7 was quantitatively detected easily by detecting the Raman intensity of the test lines. Under optimal conditions, the limit of detection (LOD) of the SiO2/Au-based SERS-LIFA strips for the target bacteria was 50 cells/mL in PBS solution, indicating these strips are 2000 times more sensitive than colloidal Au-based LFIA strips. Moreover, the proposed assay demonstrated high applicability in E. coli O157:H7 detection in biological samples, including tap water, milk, human urine, lettuce extract and beef, with a low LOD of 100 cells/mL. Results indicate that the proposed SERS-based LFIA strip is applicable for the sensitive and quantitative determination of E. coli O157:H7.